The kitchen and the multinational corporation: An analysis of the links between the household and global corporations - Rosenberg, Harriet (Journal of business ethics, 1987)
The paper examines relationships between multinational corporations and the unwaged work women do in their homes. It is argued that far from being a sanctuary, the home has become a dumpsite for unnecessary and unsafe products. Women in North America and the Third World are now dealing with health and safety issues in their neighbourhoods and households. Consciousness of these dangers has resulted in mobilization and the formation of alliances aimed at confronting multinationals and securing more government regulation. The experience of one group of women in a small Ontario community is described.